Transurethral ultrasound therapy of the prostate in the presence of calcifications: A simulation study - Suomi, Visa; Treeby, Bradley; Jaros, Jiri; Makela, Pietari; Anttinen, Mikael; Saunavaara, Jani; Sainio, Teija; Kiviniemi, Aida; Blanco, Roberto (Medical physics, 2018)
PURPOSE: Transurethral ultrasound therapy is an investigational treatment modality which could potentially be used for the localized treatment of prostate cancer. One of the limiting factors of this therapy is prostatic calcifications. These attenuate and reflect ultrasound and thus reduce the efficacy of the heating. The aim of this study is to investigate how prostatic calcifications affect therapeutic efficacy, and to identify the best sonication strategy when calcifications are present. METHODS: Realistic computational models were used on clinical patient data in order to simulate different therapeutic situations with naturally occurring calcifications as well as artificial calcifications of different sizes (1-10 mm) and distances (5-15 mm). Furthermore, different sonication strategies were tested in order to deliver therapy to the untreated tissue regions behind the calcifications. RESULTS: The presence of calcifications in front of the ultrasound field was found to increase the peak pressure by 100% on average while the maximum temperature only rose by 9% during a 20-s sonication. Losses in ultrasound energy were due to the relatively large acoustic impedance mismatch between the prostate tissue and the calcifications (1.63 vs 3.20 MRayl) and high attenuation coefficient (0.78 vs 2.64 dB/MHz1.1 /cm), which together left untreated tissue regions behind the calcifications. In addition, elevated temperatures were seen in the region between the transducer and the calcifications. Lower sonication frequencies (1-4 MHz) were not able to penetrate through the calcifications effectively, but longer sonication durations (20-60 s) with selective transducer elements were effective in treating the tissue regions behind the calcifications. CONCLUSIONS: Prostatic calcifications limit the reach of therapeutic ultrasound treatment due to reflections and attenuation. The tissue regions behind the calcifications can possibly be treated using longer sonication durations combined with proper transducer element selection. However, caution should be taken with calcifications located close to sensitive organs such as the urethra, bladder neck, or rectal wall.
Keywords: prostata; Ultrasonic Therapy; calcification; Prostate; prostate cancer; Tomography, X-Ray Computed; Urethra; Calcinosis; lidé; heating; uretra; ultrazvuková terapie; therapeutic ultrasound; Male; počítačová rentgenová tomografie; mužské pohlaví; efficacy; kalcinóza; Humans